Teacher-Student Relationships and Pupil Math Anxiety: A Longitudinal Study - Zhang, Li (Best Evidence in Chinese Education, 2025)
The teacher-student relationship plays a supporting role in student learning. Are there any mutual influences between the teacher-student relationship and student math anxiety? This study aims to examine the longitudinal interaction between the teacher-student relationship and math anxiety in primary school students with a sample of 221 pupils aged 9 and 10 from X School in Chongqing City in China. The study went through two sessions of investigation with an interval of one year.